Evaluating women’s experiences and satisfaction with labour induction in India: a comparison of the participant generated experience and satisfaction (PaGES) index with standard methods - Avni Patel; Rachel Howard; Brian Faragher; Jill Durocher; Beverly Winikoff; Andrew Symon; Andrew Weeks; Shuchita Mundle; Kate Lightly (BMC Pregnancy and Childbirth)
Abstract Background Although induction of labour is becoming more common worldwide, there are few studies that assess women’s satisfaction with it. The newly developed Participant Generated Experience and Satisfaction (PaGES) Index collects brief qualitative data and quantifies it, allowing detailed satisfaction data to be collected on large populations. The PaGES data has never previously been compared to other methods of assessing study participants’ satisfaction. We aimed to triangulate PaGES Index, Likert questionnaire and interview data from a large, randomised trial of labour induction to fully understand women’s priorities, experience and satisfaction and to compare the findings of the three instruments. Methods A convergent parallel multi-methods research design was used. Participants in the Misoprostol or Oxytocin for Labour Induction (MOLI) trial (n = 520) completed the PaGES Index before and after birth, listing priorities and allocating spending points to demonstrate their relative importance. Postpartum, participants scored their satisfaction with each item. Quantitative data was collected following birth on the acceptability of augmentation, delivery time, pain and anxiety using a Likert scale. Semi-structured interviews were also conducted, and thematic analysis was carried out using a framework approach. The data from 20 participants who had completed all three outcome measures were integrated and compared. Results Although common themes, such as pain, emerged from participants’ responses to the three instruments, each provided different insights. The Likert responses demonstrated overall satisfaction with the induction process but with high levels of pain and anxiety. Semi-structured interviews highlighted that safety and health of the baby was a key priority. The PaGES Index confirmed that the baby’s wellbeing was most important to women, but women also expressed a strong preference for vaginal delivery. Conclusions The PaGES Index, Likert questionnaire and semi-structured interview data provide varied but complimentary insights on women’s birth experiences and their satisfaction with their induction process. The outputs of the three methods align, but the PaGES index was unique in capturing both detailed qualitative and quantitative information for all study participants. Trial registration The MOLI study is registered in ClinicalTrials.gov (NCT03749902, Registration date: 21st Nov 2018) and Clinical Trial Registry, India (CTRI/2019/04/018827).